Identify physiological traits to increase yield potential through enhanced biomass, spike fertility and optimized source-sink balance in wheat (Triticum aestivum L.) genotypes - Trujillo Negrellos, Eliseo (2016)
Increased demand for food, climate change and greater dependence on food imports in less developed countries represent a challenge to achieve global food security. Wheat (Triticum aestivum L.) is the most widely grown crop and an essential component in ensuring global food security. Therefore, breeders need to develop new cultivars with higher grain yield potential. One physiological avenue to raise yield potential is by improving the allocation of assimilate to the spike during stem elongation to enhance grains m-2 and harvest index (proportion of above-ground dry matter at harvest in grain; HI). Partitioning to spikes could be increased to enhance floret survival by reducing competition from alternative sinks, including roots, leaves, stems and infertile tillers (Foulkes et al., 2011). However, attention must also be paid to maintaining post-anthesis source (photosynthetic capacity) to ensure grain growth of new cultivars is not source-limited. Although yield grains in wheat have historically been associated with traits influencing the capacity of the grains to store assimilate (sink), rather than influencing potential assimilate production (source), there is some evidence that modern cultivars are moving closer towards source limitation of grain growth (Acreche and Slafer 2009). So it is important to quantify the source and sink balance in CIMMYT elite germplasm and its physiological determinants to guide further strategies for yield potential improvement. The objectives of this study were to: i) Identify physiological traits determining enhanced above-ground biomass per unit area and radiation-use-efficiency (above-ground biomass per unit photosynthetically active radiation (PAR) interception; RUEPAR), spike fertility and HI in modern high biomass CIMMYT spring wheat germplasm, ii) quantify post-anthesis source: sink balance according to responses to a degraining to source-sink manipulation treatment, and iii) identify marker-trait associations for grain weight response to degraining (as an indication of source-sink balance) and senescence-related traits. In this study, a panel of twenty six elite CIMMYT spring wheat cultivars and a wheat association mapping (WAMI) panel of 294 genotypes comprising advanced lines and cultivars were evaluated in replicated field experiments under full irrigation in NW Mexico. The 26 cultivar panel was grown in in three seasons (2010-11, 2011-12 and 2012-13) and the WAMI panel in two seasons (2012-13 and 2013-14). In the 26 cultivar panel, growth analysis was carried at key development stages to assess above-ground dry matter (AGDM), DM partitioning and green canopy area. Assessment of fractional PAR interception by the canopy was carried out during the stem-elongation phase (GS31-GS65+7d) and RUEPAR was calculated over this phase in 2011-12 and 2012-13. Flag-leaf stomatal conductance was measured at around anthesis and senescence parameters were assessed at the canopy level and at leaf level. In both the 26 cultivar panel and the WAMI panel experiments, a degraining treatment was carried out at anthesis (GS65) +7-14 days by removing half of the spikelets to assess grain weight responses compared to control spikes as an indicator of source-sink balance and leaf and canopy senescence parameters were quantified in the control treatment. In the 26 cultivar panel, grain yield variation was associated more strongly with AGDM at harvest than HI; and biomass was positively associated with year of release. Radiation-use efficiency during stem elongation (GS61 – GS65+7d) showed genetic variation in one year out of two in which this trait was measured and a positive association with crop growth rate (AGDM g m-2 d-1) and with flag-leaf nitrogen (N) content. Furthermore, both flag-leaf stomatal conductance at anthesis and RUEPAR showed a positive association with grain yield among the 26 cultivars. There was genetic variation in each of spike partitioning index (proportion of AGDM as spike at GS65+7d) and fruiting efficiency (grain per g spike DM at GS61+7d) positively associated with grains m-2 amongst the 26 genotypes, and there was no trade-off between SPI and FE. Fruiting efficiency was associated with a greater proportion of lemma DM within the spike morphological components (glume, rachis, lemma, palea and awn). Results showed there is scope to increase biomass through RUEPAR and RUEPAR could be enhanced by selecting for increased stomatal conductance and/or flag-leaf N content. Grain weight responses to the degraining treatment in both the 26 cultivar panel and the WAMI panel showed that grain growth was either sink limited or co-limited by sink and source in the genotypes. In both panels, genotypes with higher grain yield showed higher grain weight responses to degraining (indicating a greater extent of source limitation); and greater grain weight responses were associated with faster senescence rate, supporting a co-limitation of source and sink in modern high yielding CIMMYT spring wheat cultivars. The genetic association mapping analysis identified a marker-trait association for grain weight response to degraining (an indicator of source-sink balance) on chromosome 7A in the WAMI panel. Grain m-2 was not associated with grain yield indicating that grain weight at some extent is driving gains to grain yield due to its positive association with year of release. Grain yield positively correlated with response to degraining over years, grain weight response to degraining was negatively associated with Flag leaf senescence in the WAMI population. Genetic variation in radiation interception by the canopy during stem elongation from GS31 to GS65+7d positively associated with accumulated above-ground dry matter amongst the CIMCOG genotypes. There was genetic variation in radiation-use efficiency (in 2013) during stem elongation and RUE was positively related with above-ground biomass at anthesis amongst the CIMCOG genotypes. Therefore, in order to increase grain yield is necessary to increase simultaneously source and sink traits.